Association of morphine vs. fentanyl prescription dispensation with adverse clinical outcomes - Reyes, Carlen; Pou, Maria Antonia; Diaz-Torne, Cesar; Carbonell-Abella, Cristina; Brotons, Carlos; Martinez-Laguna, Daniel (Frontiers in Pharmacology, 2025)
IntroductionThe aim was to assess the associations between morphine, fentanyl and adverse events in primary care patients.MethodsA retrospective, propensity-score-weighted cohort study using a primary-care database covering >75% population of Catalonia, Spain was conducted. Patients aged ≥18 years with ≥1 year of available data and incident dispensation of morphine or fentanyl, were included from 1st January 2007 to 31st December 2017. Outcomes were all-cause mortality, cardiac arrhythmias, fractures (hip, pelvis, vertebra, wrist, humerus), constipation, delirium, falls, opioid abuse/dependence, and sleep disorders while on treatment. Risk ratios (RRs) and hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using cause-specific Cox models.ResultsA total of 12,632 patients (3,040 with morphine and 9,695 with fentanyl) were included (median [IQR] age, 78.4 [63.8; 86.1] years; 63.6% female). Compared with morphine, fentanyl dispensation was associated with a higher risk of fractures (incidence: 6.92 vs. 4.13 per 1,000 dispensations-month; HR, 1.63 [95% CI, 1.15–2.32]; RR, 1.78 [95% CI, 1.25–2.53]), especially in men and in those <65 and over >80 years old. No difference was observed for the rest of outcomes.ConclusionAmong outpatients, a new prescription dispensation of fentanyl, compared with morphine, was associated with a higher risk of fractures. The findings should be interpreted cautiously given the potential for residual confounding.